Effectiveness of discharge education for patients undergoing general surgery: A systematic review and meta-analysis. (April 2023) - Gillespie, Brigid M.; Thalib, Lukman; Harbeck, Emma; Tobiano, Georgia; Kang, Evelyn; Tobiano, Steve; Tong, Mavis; Clark, Justin; Patel, Bhavik; Chaboyer, Wendy
Abstract: Background: There is some evidence to suggest that discharge education may reduce the risk of postoperative complications, however, a critical evaluation of the body of evidence is needed. Objective: To assess the effect of discharge education interventions versus standard education given to general surgery patients prior to, or up to 30-days of hospital discharge on clinical and patient-reported outcomes. Design: Systematic review and meta-analysis. Clinical outcomes were 30-day surgical site infection incidence and re-admission up to 28 days. Patient-reported outcomes included patient knowledge, self-confidence, satisfaction, and quality of life. Setting: Participants were recruited from hospitals. Participants: Adult general surgical patients. Methods: MEDLINE (Pubmed), CINAHL (EBSCO), EMBASE (Elsevier) and the Cochrane Library were searched in February 2022. Randomised controlled trials and non-randomised studies of interventions published between 2010 and 2022, with adults undergoing general surgical procedures receiving discharge education on surgical recovery, including wound management, were eligible for inclusion. Quality appraisal was undertaken using the Cochrane Risk of Bias 2 and the Risk of Bias Assessment Tool for Nonrandomised Studies. The Grading of Assessment, Development, Recommendations, and Evaluation was used to assess the certainty of the body of evidence based on the outcomes of interest. Results: Ten eligible studies (eight randomised control trials and two non-randomised studies of interventions) with 965 patients were included. Six randomised control trials assessed the effect of discharge education interventions on 28-day readmission (Odds ratio 0.88, 95 % confidence interval 0.56–1.38). Two randomised control trials assessed the effect of discharge education interventions on surgical site infection incidence (Odds ratio = 0.84, 95 % confidence interval 0.39–1.82). The results of the non-randomised studies of interventions were not pooled due to heterogeneity in outcome measures. The risk of bias was either moderate or high for all outcomes, and the body of evidence using GRADE was judged as very low for all outcomes studied. Conclusions: The impact of discharge education on the clinical and patient-reported outcomes of patients undergoing general surgery cannot be determined due to the uncertainty of the evidence base. Despite the increased use of web-based interventions to deliver discharge education to general surgery patients, larger samples in more rigorous multicentre randomised control trials with parallel process evaluations are needed to better understand the effect of discharge education on clinical and patient-reported outcomes. Registration: PROSPERO CRD42021285392. Tweetable abstract: Discharge education may reduce the likelihood of surgical site infection and hospital readmission but the body of evidence is inconclusive.